Corruption practices in drug prescribing in Vietnam - an analysis based on qualitative interviews - Tuan A. Nguyen; Rosemary Knight; Andrea Mant; Husna Razee; Geoffrey Brooks; Thu H. Dang; Elizabeth E. Roughead (BMC, 2018)
Abstract Background Results from a previous study showed that 40 to 60% of the price of off-patent medicines in Vietnam was typically spent to induce prescribers to use the medicines, and to persuade procurement officers within hospitals to buy them. In this article we examine how and why inducements were paid by the pharmaceutical industry to health care providers in Vietnam. Methods We use a theoretically informed analysis to understand pharmaceutical companies' account of giving inducements and prescribers' account of taking them, elicited through in-depth interviews. Results Analysis of the emergent concepts derived from our qualitative data led to viewing the constructs from the theoretical framework of opportunities; pressures; and rationalization within a hierarchy of systemic factors and individual factors. Economic survival pressures in an imperfectly competitive market reportedly encouraged pharmaceutical companies and prescribers to be linked financially. Although individual factors such as professional ethics and personal values influenced doctors' responses to corrupt practices, entrenched systemic issues, including lack of transparency, accountability, poor enforcement of legislation and prevalence of corruption emerged as important factors supporting corrupt practice or even making it very difficult for individuals to opt out of corrupt practices. Conclusions Our theoretically informed analysis of inducements provides an in-depth understanding of an angle of corruption in Vietnam's health sector, showing the need for multifaceted strategies in the fight against corruption in the health sector. Remedial strategies need to address both systemic and individual factors including interventions to relieve dependencies for survival of health care services on the corrupt system.